Studi Teologi Terhadap Realitas Kesenjangan Wacana dan Tingkah Laku Politisi di Zaman Kali Yuga - Putu Dana Yasa; Kadek Yogi Sumertayasa; Made Joniarta (Sphatika: Jurnal Teologi, 2023)
Hearing the word politics today is as if hearing terms that are full of deception, the public's trust has been hurt so deeply as a result of the behavior of politicians who don't match their words and actions. This paper attempts to convey several theological teachings that should serve as guidelines for politicians, although in reality not many realize that there are so many theological teachings that should serve as a guide for a leader. This study provides some literature on how important it is for Hindu leaders to realize that their duties as leaders are very noble as God's representatives to manage the universe. A politician must be aware that he is a representative of the people whose job is to provide welfare for his people. Politicians must consciously try to change the negative stigma in society that politics is a science filled with the art of deception. This study will fundamentally strengthen awareness so that theology as a science can not only be a theory but can contribute to the life of a politician as the main guideline for carrying out their duties.